AN ANALYSIS OF GOMORY CUTTING PLANE METHOD APPLICATION IN THE OPTIMIZATION OF PRODUCTION PROFIT: A CASE STUDY OF GRIYA BATIK NOTONEGORO JEMBER - Yunta, Girlyas Rasta; Setiawani, Susi; Prihandini, Rafiantika Megahnia (PATTIMURA UNIVERSITY, 2023)
Gomory cutting plane method is one of the methods in linear programming that is needed to solve integer programming when the decision obtained is in the form of fractions with the addition of constraint known as gomory constraint. The purpose of this research is to determine the best optimum solution by maximizing the profit of batik production using the gomory cutting plane method. This type of research is applied research using a quantitative approach. Data collection methods used are interviews and documentation. This research is focused on four kinds of Jember batik motifs which are the best-selling, namely mbako semak batik cloth; sekar jagad batik cloth; kopi daun batik cloth; and parakopi batik cloth. The results showed that there was an increase in profit of or per production when using the simplex method assisted by QM for Windows V5 software. Meanwhile, to make batik cloth, integer values are needed in the form of integers. Therefore, the application of gomory cutting plane method in optimizing the profit of batik production is very appropriate to use with the obtained maximum settlement of which occurs when sheets, sheets, sheets, and sheets.